Case study on the carbon consumption of two metropolitan cities. - Heinonen, Jukka (The International Journal of Life Cycle Assessment)
Purpose The cities merit special attention in global warming since they produce up to 80 percent of the global greenhouse gas emissions. Even though this has been widely acknowledged, only few papers exist that have studied cities holistically from a demand, i.e., consumption, perspective. The study presents a detailed analysis of the carbon footprint of two metropolitan cities from a consumption perspective. With the analysis of consumer carbon footprints (carbon consumption), the distribution of emissions in the key source categories is presented and compared. Materials and methods The study utilizes Finnish consumer survey data by cities, regional emission data for key processes, and general emission data to produce a hybrid LCA model for a holistic assessment of city level green house gas emissions from the consumption perspective. Results and discussion The study results showed the carbon consumption to be 13.2 t CO2e per person in Helsinki with a 17,400 E annual consumption expenditure and 10.3 t CO2e per person in Porvoo with a 15,900 E annual consumption expenditure, respectively. The dominant carbon sources for metropolitan living are heat and electricity, building and property, private driving and services. Within the cities, some significant differences were found. The carbon emissions from energy consumption are 4.5 t CO2e for an average consumer in Helsinki, whereas an average consumer in Porvoo only causes 2.0 t CO2e due to the cleaner energy production in Porvoo. On the other hand, private driving causes 2.0 t CO2e in Porvoo, but only 1.3 t in Helsinki. The overall trip generation in Helsinki is only half of that in Porvoo, and also, the usage of public transport is at a substantially higher level in Helsinki. The current results contradict interestingly some earlier studies in finding that the theoretical carbon reducing influence of city density is overriden with oter factors, such as the type of energy production, energy efficiency of the housing stock, and increased use of services. In our study, Helsinki represents a metropolitan area with a denser structure and a more efficient public transport system, but still consuming around 25 percent more carbon emissions than the other city in the metropolitan area, Porvoo. The sensitivity analysis showed that even with the normalization of the key parameters between the two cities, the main finding still holds. Conclusions The evaluation of the carbon footprint of cities from the consumption perspective, instead of a more traditional production perspective, seems to offer an interesting new insight into the carbon footprints of the cities. It identifies similar key sources of carbon as production oriented studies but further emphasizes the significance of the utilized services in the carbon footprint evaluations. In the future, the carbon footprint of services, especially in the service intensive economies and cities that tend to outsource their manufacturing and carbon emissions, should be further examined since they cause an ever increasing proportion of the carbon consumption of consumers.